Optimization Studies Of Batch Polymerization For Polystyrene Process - Azman, Nurshahida (2013)
Polymerization is a chemical reaction process of monomer molecules to form a polymer chain. In the polymer industry, batch polymerization reactors are used extensively to manufacture a variety of polymers of numerous grades. Batch process is well suited for low-volume products and for products with numerous grades (as in specialty polymers. However, this process may require higher operation cost because it can achieve high conversion with long batch time. The operation is unsteady-state where the composition and temperature always change with time. Optimum operating conditions are very important for the polymerization process in order to achieve the objective function in the process. In this study, the optimization technique using mathematical models was implemented to obtain those optimum operating conditions. The dynamic optimization problem was solved using an orthogonal collocation method where the differential variables were fully discretized. Collocation method is one of the methods that can be used to solve dynamic optimization. In the case of solving the dynamic optimization problems, collocation formulae can be used to transform the ordinary differential equations into algebraic equations. In this study, the optimization of optimal temperature generations in batch process of polystyrene was investigated theoretically.